Propuesta para el rediseño del plan de Mantenimiento del Remolcador Cartagena de la empresa Naviera Central ubicada en la ciudad de Barranquilla Atlántico (2022)
A proposal is presented to generate a redesign of an operational maintenance plan for a series of machinery components of the Cartagena Tugboat from the Central Shipping Company, a tug used for river transport from the port of Barrancabermeja to the port of Cartagena. The main purpose of the proposal is the opportunity to extend the useful life of the components of this tugboat, which in turn allows to contribute to the productivity of the organization by decreasing the replacement of components due to unexpected failures, the reduction of costs and unplanned resources. For the redesign of the maintenance plan in its development phase, an analysis of the current maintenance processes of the Cartagena Tugboat equipment must be carried out, and with it methods and tools focused on the preventive maintenance methodology are applied. With this, generate a new maintenance planning route for the equipment of the Cartagena Tugboat, improving the use of resources and operating times.